Cardiovascular disease prevention: Community Based Asset Mapping within religious networks in a rural Sub-Saharan African neighbourhood. - Andrew Willis; Samuel Chatio; Natalie Darko; Engelbert A Nonterah; Sawudatu Zakariah-Akoto; Joseph Alale; Ceri R Jones; Ffion Curtis; Setor Kunutsor; Patrick O Ansah; Sam Seidu (Public Library of Science (PLoS), 2023)
Prevalence of conditions which raise cardiovascular risk, such as hypertension and type 2 diabetes are seeing a dramatic rise in Sub Saharan Africa. A large proportion of these cases remain undiagnosed and there is limited resource to provide patients with self-management support and education once diagnosed. This study aimed to identify and catalogue community-based assets for the purposes of developing and deploying a screening and education programme for cardiometabolic risk factors (diabetes and hypertension) within religious organisations in a local community in a rural Ghanaian context. We utilised a community-based form of participatory research made up of a number of different components including community-based asset mapping and stakeholder consultation, supplemented by 18 in-depth interviews and 10 focus groups with n = 115 service users, to map existing assets with relevance to cardiometabolic health in this setting and context. Thematic analysis of interview and focus group data was performed to identify themes related to successful implementation of health screening. Two stakeholder workshops with local healthcare professionals, faith leaders and health policy makers were delivered to co-produced a prioritised list of recommendations and 'asset map' to aid deployment of mass screening within faith organisations in this context. The findings of this research highlight a number of 'hidden' community assets and motivational mechanisms at an individual, community and institutional levels; these have informed a list of recommendations which have been co-developed with the stakeholder group and local community to support the development of effective screening strategies for cardiometabolic conditions within faith organisations in this context. We have identified key mechanisms and assets which would support a sustainable screening approach designed to engage an underserved community at high CVD risk to promote general community health and well-being.